Analisis Dampak Wisata Religi Terhadap Peningkatan Ekonomi Street Vendors di Kawasan Masjid Agung Al-Anwar Kota Pasuruan - Wahyu Nurfebieni; Moh. Mukhsinin Syu’aibi; Ifdholul Maghfur (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
Religious tourism encompasses travel experiences connected to faith, history, culture, traditions, and local beliefs, supporting existing Islamic values and culture. This study aims to delve into the potential and impact of religious tourism on the economic upliftment of street vendors around the Al-Anwar Grand Mosque in Pasuruan City. Employing a descriptive qualitative method, the research gathered primary and secondary data through surveys, interviews, and observations conducted at the Al-Anwar Grand Mosque in Kebonsari, Panggungrejo District, Pasuruan City. The findings reveal that religious tourism plays a significant role in boosting income and creating employment opportunities for street vendors near the mosque. Available facilities and services like parking areas, green spaces, information centers, and social activities further support the economic activities of these vendors. Positive impacts are also experienced by visitors and the local government, including increased shopping options, higher tax revenue, and infrastructure development. This research provides a deeper understanding of the contribution of religious tourism to the local economy and the importance of empowering street vendors in the development of tourism in Pasuruan City.